تنفيذ تعليم اللغة العربية في ترقية مهارات القراءة لطلاب الصف العاشر مدرسة الثانوية الإسلامية مشكات الأنوار جومبانج - Annabiil, Muhammad Aghthof (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
This article aims to examine reading skills, which are one of the language skills taught to students in learning Arabic. Reading is translating written letters into meaning or giving meaning to printed words. This is a dual process. In tenth grade, students learn reading skills while teaching Arabic every Wednesday and Thursday at seven to eight. This learning has a big impact on students in their daily life at Islamic boarding schools and cannot be separated from the study of heritage books. The research questions for this study are: (1) How is Arabic language teaching implemented for class X students at Misykat Al Anwar Islamic High School Jombang? (2) How do reading skills improve in class X at Misykat Al Anwar Islamic High School Jombang? (3) What are the motivations and obstacles in implementing Arabic language learning in class 10 of Misykat Al Anwar Islamic High School Jombang? This research method is qualitative research with a descriptive approach. This type of research uses case study research. Data collection through observation, interviews and documentation. The data in this research was analyzed by means of data reduction, data presentation, and drawing conclusions. Researchers try to verify the validity of the data by expanding research and triangulation (sources, techniques and time).